Indigenous Peoples' Data During COVID-19: From External to Internal - Carroll, Stephanie Russo; Akee, Randall; Chung, Pyrou; Cormack, Donna; Kukutai, Tahu; Lovett, Raymond; Suina, Michele; Rowe, Robyn K. (Frontiers in Sociology, 2021)
Global disease trackers quantifying the size, spread, and distribution of COVID-19 illustrate the power of data during the pandemic. Data are required for decision-making, planning, mitigation, surveillance, and monitoring the equity of responses. There are dual concerns about the availability and suppression of COVID-19 data; due to historic and ongoing racism and exclusion, publicly available data can be both beneficial and harmful. Systemic policies related to genocide and racism, and historic and ongoing marginalization, have led to limitations in quality, quantity, access, and use of Indigenous Peoples' COVID-19 data. Governments, non-profits, researchers, and other institutions must collaborate with Indigenous Peoples on their own terms to improve access to and use of data for effective public health responses to COVID-19.